ผลของวัสดุเคลือบหลุมร่องฟันที่ปลดปล่อยฟลูออไรด์ได้ต่อการคืนกลับแร่ธาตุของรอยผุจำลองระยะแรกในห้องปฏิบัติการ - อัญรัตน์ มหาสะโร (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study aimed to evaluate the remineralization effect of fluoride-releasing materials on artificial caries lesions. 75 enamel artificial caries specimens (150 µm depth) were randomly divided into 5 groups: a surface-prereaction type glass ionomer filler-containing sealant (S-PRG sealant; BeautiSealant), a glass-ionomer cement (GIC; FujiVII), a fluoride-containing sealant (F-sealant; DeltonFS+), a conventional sealant (Delton), and un-coated (Control). All groups underwent thermocycling 500 cycles and pH-cycling for 5 days. Pre- and post-experiment mineral density (MD) of lesions were evaluated by micro- computed tomography (micro-CT). After the experiment, MD of the 4 material groups increased while control group decreased significantly. Percent MD change of the 4 material groups increased significantly than the control group. The highest increase of MD the caries lesion was GIC, followed by F-sealant, S-PRG sealant and conventional sealant. The percent MD change of GIC and F-sealant significant higher and deeper than the conventional sealant. However, the 3 fluoride material groups showed no significant difference. Sealants inhibited demineralization and promoted remineralization of artificial initial caries. Fluoride sealant yielded higher quantity and quality of remineralization (increase in mineral density and depth of remineralization).